Bankruptcy Analysis Using Altman Z-Score Model and Springate Model In Retail Trading Company Listed In Indonesia Stock Exchange - Erni Prasetiyani; Moh. Sofyan (Yayasan Ilomata, 2020)
The business environment in the retail experience turbulence, strong now many companies to reduce the impact outlets greater losses. Reduction in earnings a problem most of all , and this has potential in bankruptcy retail company in the future This research is analyzing about retail companies affected by the deterioration in performance that has been registered in Indonesia Stock Exchange. Model and data processing used to calculate potential harm is a model altman z score and models springate. Discussion result there is a retail companies go public has the potential to be the calculated use bankruptcy model altman z score as well as a model springate namely pt modern. international. Information , proceedings in potential for bankruptcy at annual report is not disclosure , was recommended to the stakeholders to oblige any new issuers give this information in the annual financial report made that release every year. To be accurate information and credible over the companies condition the truth.